2013
DOI: 10.9778/cmajo.20120039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implementing electronic medical records on primary care billings and payments: a before-after study

Abstract: Implementation of EMRs by primary care physicians did not result in decreased billings or government payments for office visits. Further economic analyses are needed to measure the effects of EMR implementation on productivity and the costs of implementing an EMR system, including the costs of nonclinical work by physicians and their staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…EMRALD physicians were found to be younger, more likely to be female, to be a Canadian medical graduate and to participate in patient-enrolment models compared to the general physician population in Ontario. [ 29 ] However, this likely reflects the characteristics of physicians who have adopted EMR software and trends in the primary care workforce. Ontario has been undergoing a primary care reform for more than a decade where the new primary care models require ‘rostering’ of patients (patient-enrollment models) and the physician acts as the their most responsible physician.…”
Section: Discussionmentioning
confidence: 99%
“…EMRALD physicians were found to be younger, more likely to be female, to be a Canadian medical graduate and to participate in patient-enrolment models compared to the general physician population in Ontario. [ 29 ] However, this likely reflects the characteristics of physicians who have adopted EMR software and trends in the primary care workforce. Ontario has been undergoing a primary care reform for more than a decade where the new primary care models require ‘rostering’ of patients (patient-enrollment models) and the physician acts as the their most responsible physician.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a survey of Ontario physicians in 2013 reported that 78% were using an EMR in their office 22 and patients in the EMRALD database have similar characteristics to the general population. 23 However, some patients not accessing the healthcare system may be missed. Secondly, we were unable to review all 73,003 adult charts, but instead reviewed only those meeting pre-defined nomenclature suggestive of MS.…”
Section: Discussionmentioning
confidence: 99%
“…While we identified an optimal administrative drug algorithm in adults aged ≥20, we recognized a prescription database is limited to those aged ≥65. Although differences in population mix may impact the generalizability of our results, this study was done on a population that is similar to the Ontario population in terms of sex, age and presence of comorbid conditions [25]; therefore, we believe our findings to be reasonably generalizable, if not only in Ontario but to the rest of Canada and has the potential to inform other countries with similar administrative databases.…”
Section: Discussionmentioning
confidence: 99%